INDEPENDENT MOTOR-PLAY ACTIVITY OF CHILDREN 5-10 YEARS OLD IN THE YARD SPACE - Voloshina, L.N.; Kondakov, V.L.; Kopeikina, E.N.; Panasenko, K.E. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the use of the spatial environment and the motor experience acquired by children in educational institutions in independent motor-playing activities. Methods and structure of the study. Observations were carried out on weekends, in the fall of 2022 in Belgorod, 682 children were covered, of which 395 were boys and 287 were girls aged 5-10 years. The results of observations were recorded in the protocol of observations. To analyze the results obtained, a ranking of the types of independent motor activity of children during walks in the yard was carried out. Results and conclusions. The limited motor experience of preschoolers, the destruction of the play space of childhood, the disappearance of folk traditions in the organization of motor activity reduce the possibility of transferring spiritual values and attitudes through time and space, national experience in the organization of motor-play activity. Children do not master the order and rules of social behavior, interpersonal relationships. And, as a result, there are problems of social development of the personality, psycho-emotional stress, maladaptation.